PERANAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK ) DALAM MENGGERAKKAN PARTISIPASI MASYARAKAT DESA( SUATU STUDI DI DESA ONGKAU I KABUPATEN MINAHASA SELATAN - RANTUNG, JOAN; MANDEY, JANTJE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2014)
Ongkau Village Is One Of Some Village Which Using The Empowerment Of FamilyProsperity Program In Actuating Society’s Participation For Increasing Village’s Development And It’sFamily Prosperity. There Are Many Programs Of Empowerment Of Family Prosperity Which HaveApplied To Ongkau Village. This Reacrh Foccusing On Education Program And Skils, EnternalEnvironment, And Public Health. The problems in this villages are unactivated of societies and humanresource not at all to have an ability and uncompetated.Purpose Of This Research Is To Know How The empowerment of family prosperity program inactuating society’s participation for increasing village’s development. The methods to used in thisresearch is quantitative methods with twenty eight responden’s.Result of this research showed relation between two variable’s not strong. Becase the value ofkoeficien kontingensi = 0,1792 more than less from the value of Cmaximum kontingensi = 0, 4082.Key words : Empowerment Of Family Prosperity, Society Participation